The Work Environment Impact toward Employee Performance at PRL Hotel - Ari Kusuma Dewi, Ni Made; Diwyarthi, Ni Desak Made Santi; Sri Sadjuni, Ni Luh Gde (Journal of Hotel Management, 2025)
A comfortable work environment, characterized by a company leadership that treats employees equally and colleagues who are supportive in assisting and interacting with each other, will result in a pleasant working atmosphere, leading to improved employee performance. A positive work environment can make a significant contribution to employee performance, while a negative work environment can have a detrimental impact on employee performance. This research was conducted at Hotel PRL with the aim of examining the influence of the work environment on employee performance at Hotel PRL. The population of this study involved all employees at Hotel PRL with a total of 582 individuals at the supervisor and staff levels. The sample for this study consisted of 85 respondents. The sampling technique used in this study was probability sampling with proportionate stratified random sampling due to the heterogeneous nature of the study population. Data was collected by distributing questionnaires using a 5-point Likert scale to measure 24 statement items. The data analysis techniques employed in this study included simple linear analysis, t-tests, and determination coefficients processed using SPSS version 29 for Windows. The results of this study indicated that the work environment has a positive and significant effect of 79,8% on employee performance at Hotel PRL.